The Concept of “Homeland” in the Kalmyk Language (based on lexicographic and folklore material) - Galina B. Esenova; Tamara S. Esenova (Монголоведение)
Introduction. The article is devoted to the universal concept “homeland”, which occupies an important place in the world picture of the Kalmyks and determines a person’s worldview. Goals. The paper attempts an insight into the concept of homeland in the Kalmyk language. Tasks: a) to establish its conceptual content; b) to characterize its figurative and axiological components; c) to determine the postulates of behavior conditioned by this concept. Material: dictionary definitions of linguistic units representing the concept “motherland”. Research methods: methods of comparative, lexical-semantic and linguocultural analysis. Results. The analysis has shown that in the Kalmyk language there are various means of objectification of the concept “motherland”, which belong to the basic lexicon, etymologized on the Mongolian linguistic soil. Conclusions. The mental object «motherland» is associated with the space (hazr, orn), where a person was born (törskn/ törsn hazr), where he lives (nutg), with water sources (usn). The perceptual image of the homeland is visualized as a territory with soft earth (dzhöln hazr), green lush grass (nohan sör), warm air (dulan), healing water (arshan). Enkr chazr-usn ‘dear motherland’, eedzh-aavin nutg ‘mother-father’s nutg’ is the highest value of the Kalmyk (törl ek met), and is presented as ‘his space’ (evrä hazr-usn), opposed to ‘foreign land’ (khärin hazr). The postulates of behavior regarding the homeland: to cherish and love the homeland, to give one’s life for the homeland, to return to the homeland, to know its customs.